2015
DOI: 10.5811/westjem.2015.2.24124
|View full text |Cite
|
Sign up to set email alerts
|

Self-Reported Provider Safety in an Urban Emergency Medical System

Abstract: IntroductionEmergency Medical Service (EMS) personnel often respond to dangerous scenes and encounter hostile individuals without police support. No recent data describes the frequency of physical or verbal assaults or which providers have increased fear for their safety. This information may help to guide interventions to improve safety. Our objective was to describe self-reported abuse and perceptions of safety and to determine if there are differences between gender, shift, and years of experience in a busy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0
4

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 19 publications
2
16
0
4
Order By: Relevance
“…Over 90% of ED healthcare providers interviewed described personal experience with workplace violence. This is consistent with prior studies conducted in more developed countries, which have found a prevalence of violence against ED healthcare providers between 80% and 100% [5,[12][13][14].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Over 90% of ED healthcare providers interviewed described personal experience with workplace violence. This is consistent with prior studies conducted in more developed countries, which have found a prevalence of violence against ED healthcare providers between 80% and 100% [5,[12][13][14].…”
Section: Discussionsupporting
confidence: 92%
“…While most of the reported violence is verbal abuse, almost one in five providers reported experience with physical abuse. This is also consistent with prior studies conducted in higher resource settings, which demonstrate similar incidents of both verbal and physical abuse [5,13,14]. The commonalities between the patterns of workplace violence in India as compared with higher resource settings can likely be attributed to factors that make the ED especially prone to violence in general.…”
Section: Discussionsupporting
confidence: 89%
“…The studies documented the high risk of exposure to violence. Boyle and Brough found high rates of verbal abuse, while Deniz, Furin and Suserud documented that about 80% of personnel had been subjected to some form of violence . Petzäll found that about two‐thirds of EMS personnel experienced threats or violence while Rahmani found that it was 75% of respondents that had experienced workplace violence .…”
Section: Resultsmentioning
confidence: 99%
“…Several related studies 17,18,19 highlight the serious personal, organizational and professional consequences, as well as inadequate job safety, as some of the costs of violence. 20,21 Other related studies have mentioned minor and serious physical injury (eye and face injuries, bites, kicks, dislocations and fractures, bruises, and scratches) and psychological consequences such as stress irritability and headache, anxiety, depersonalization, depression, sleep disorders, irritability, fear of safety, and disturbing memories. Psychological injuries cause social consequences, including impact on social interactions, isolation, and personality changes in the workplace.…”
Section: Discussionmentioning
confidence: 99%